Final report of CCQM-K172 on measurement of Specific Adsorption A [mol/kg] of Ar on zeolite at liquid argon temperature (to enable a traceable determination of the Specific Surface Area by following ISO 9277) - Sobina, Egor; Prinz, Carsten; Landi, Sandra M; Santos, Bianca P S; Damasceno, Jailton C; Kuznetsov, Oleksii; BİLSEL, Mine; Sadak, Ali Enis; Wang, Hai (Metrologia, 2023)
The CCQM-K172 key comparison on measurement of Specific Adsorption A [mol/kg] of Ar on zeolite at liquid argon temperature (to enable a traceable determination of the Specific Surface Area by following ISO 9277) has been performed by the Surface Analysis Working Group (SAWG) of the Consultative Committee for Amount of Substance (CCQM). The objective of this key comparison is to compare the equivalency of the National Metrology Institutes (NMIs) and Designated Institutes (DIs) for the measurement of specific adsorption of Ar, BET specific surface area) of microporous substances (zeolites, sorbents, ceramics, catalytic agents, etc) used in advanced technology. In this key comparison, a commercial zeolite was supplied as a sample. Five NMIs/DIs participated in this key comparison. All participants used a gas adsorption method, here argon adsorption at 77.3 K, for analysis according to the international standard ISO 9277. In this key comparison, the degrees of equivalence uncertainties for specific adsorption argon, BET specific surface area were established. To reach the main text of this paper, click on Final Report . Note that this text is that which appears in Appendix B of the BIPM key comparison database https://www.bipm.org/kcdb/ . The final report has been peer-reviewed and approved for publication by the CCQM, according to the provisions of the CIPM Mutual Recognition Arrangement (CIPM MRA).